(3GdYQGb(B-(3bQlf ef GdEadGS(B: (3ef YGe (B1921 (3Edi Gdjhe(B/ s (3YGOd HchGfs - Adil Bakwan (3HchGf, YGOds ((3HjQhJ; s Naufal- Hachette Antoine; (3fhad (B- (3gGTjJ CfWhGfs, 2023)
Title translation- Iraq: A Century of Bankruptcy- From 1921 till today. By Adil Bakwan (3gPg bqUI HdO jMGhd, efP eGFI YGe, Cf jUHM HdkOG(B... (3jcJTa GdbGQF aj gPG GdcJGH cjGkfG YQGbkqjG cGf Gdedc ajUd bO GqJNP ef JCSjSg gOkaG dg aj YGe (B1921 (3djhqMO TjYI GdLfhH hSqfI GdhSW hcQO GdTeGd(B. (3dcqf gPG GdcjGf dG jRGd, MqJi Gdjhe, aQjSI GdJOqNdGJ GdNGQLjI GdHQjWGfqjI hGdCejQcqjI hGdEjQGfqjI Ydi GdeSJhi GdYGdej, HjfeG JbqhVg OGNdkqjG JOqNdGJ GdeDqSSI GdOjfqjI hGfJTGQ GdaSGO hSjWQI GdCMRGH Ydi ehGQO GdHdGO h(S0(3nednjTI(S1 (3GdOhdI(B. (3agd ef Cemd aj GfJgGA gPG GdJNqHW? gd JJLGhR CdhGf GdWja CdhGfgG aJHUQ GdbheqjI GdYQGbqjI GdfhQ hjSJOqd GdYQGb Edi faSg? (BThis book talks about an Iraqi entity that King Faisal aimed to establish in 1921 to unify the Shia of the south, the Sunni of the center, and the Kurds of the north. However, this entity still remains, to this day, a victim of external interventions from Britain, the United States, and Iran on a global level, while internally it is undermined by interventions from the religious establishment, the spread of corruption, the control of the country's resources by political parties, and the "militia-ization" of the state. Is there hope for an end to this turmoil? Can the different colors of the spectrum transcend their differences, allowing Iraqi nationalism to emerge and for Iraq to find itself?s
Arabic
Keywords: 1921-; JZ1305-2060 Scope of international relations. Political theory. Diplomacy; Saudi influence (3GdfahP GdSYhOjs; Iraq (3YQGbs